Infecções pelos vírus das hepatites B e C e o carcinoma hepatocelular na Amazônia oriental - MIRANDA, Esther Castello Branco Mello (2014)
In order to contribute to a better understanding of the possible role of hepatits B and C in the etiopathogenis of HCC in the East Amazon, there were studied 36 patients in Belém/PA. Serological hepatitis markers were evaluated and polymerase chain reaction assays were used to detect HBV-DNA and HCV-RNA. Alcohol abuse was observed in 33.3% and cirrhosis in 83.3%. In 88.9% of the sample, one or more hepatitis B markers were positive. Also, 8.3% those patients had anti-HCV simultaneously positive. The HBsAg serological test was positive in 58.3%; anti-HBc in 86%; anti-HBe in 85.7%; anti-HBe in 9.5%; IgM anti-HBc in 57.1%. The HBV DNA was found in 37.7% and in 65% of the HBsAg positive. The HCV RNA was detected in 8.5% and in 100% of' the patients positive to anti-HCV. The AFP was above the normal value in 88.9% of patients, with levels up to 400ng/ml in 75% of them. In conclusion, hepatitis B virus infection seems to be important in the etiology of HCC and improving measures such immunization and screening in the risk population should be emphasyzed.